Phase II randomised control feasibility trial of a nutrition and physical activity intervention after radical prostatectomy for prostate cancer. Issue 11 (6th November 2019) - Hackshaw-McGeagh, Lucy E; Penfold, Chris; Shingler, Ellie; Robles, Luke A; Perks, Claire M; Holly, Jeff M P; Rowe, Edward; Koupparis, Anthony; Bahl, Amit; Persad, Raj; Shiridzinomwa, Constance; Johnson, Lyndsey; et al.
Abstract : Objective: Dietary factors and physical activity may alter prostate cancer progression. We explored the feasibility of lifestyle interventions following radical prostatectomy for localised prostate cancer. Design: Patients were recruited into a presurgical observational cohort; following radical prostatectomy, they were offered randomisation into a 2×3 factorial randomised controlled trial (RCT). Setting: A single National Health Service trust in the South West of England, UK. Participants: Those with localised prostate cancer and listed for radical prostatectomy were invited to participate. Randomisation: Random allocation was performed by the Bristol Randomised Trial Collaboration via an online system. Interventions: Men were randomised into both a modified nutrition group (either increased vegetable and fruit, and reduced dairy milk; or lycopene supplementation; or control) and a physical activity group (brisk walking or control) for 6 months. Blinding: Only the trial statistician was blind to allocations. Primary outcome measures: Primary outcomes were measures of feasibility: randomisation rates and intervention adherence at 6 months. Collected at trial baseline, three and six months, with daily adherence reported throughout. Our intended adherence rate was 75% or above, the threshold for acceptable adherence was 90%. Results: 108 men entered the presurgical cohort, and 81 were randomised into the postsurgical RCT (randomisation rate: 93.1%) and 75 completed the trial. Of 25 men in the nutrition intervention, 10 (40.0%; 95% CI 23.4% to 59.3%) adhered to the fruit and vegetable recommendations and 18 (72.0%; 95% CI 52.4% to 85.7%) to reduced dairy intake. Adherence to lycopene (n=28), was 78.6% (95% CI 60.5% to 89.8%), while 21/39 adhered to the walking intervention (53.8%; 95% CI 38.6% to 68.4%). Most men were followed up at 6 months (75/81; 92.6%). Three 'possibly related' adverse events were indigestion, abdominal bloating and knee pain. Conclusions: Interventions were deemed feasible, with high randomisation rates and generally good adherence. A definitive RCT is proposed. Trial registration number: ISRCTN 99048944.